2000
DOI: 10.1002/j.2161-0045.2000.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Family Commitment and Attitudes Toward Feminism in Medical Students

Abstract: The authors examine work-family commitment and attitudes toward feminism in a cross-sectional, medical student sample (126 women, 145 men). Results indicated no significant gender differences in commitment levels. Third-year students reported significantly more family commitment than did students in lower years. Women reported significantly more positive attitudes toward feminism than did men. Future research should examine commitment to work and family roles relative to participation in work and family roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Nevill and Super (1988) found that undergraduate women were more committed to both work and home than undergraduate men were. Studies of undergraduate, graduate, and medical students have found no differences between men and women in their commitment levels to work and family (Covin & Brush, 1991;Hartung & Rogers, 2000). Spade and Reese (1991) found undergraduate men and women to have equally strong commitments to both work and family life; however, women seemed to place more importance on household roles, and they expected to be employed fewer hours than men did.…”
Section: Gendermentioning
confidence: 93%
See 2 more Smart Citations
“…Nevill and Super (1988) found that undergraduate women were more committed to both work and home than undergraduate men were. Studies of undergraduate, graduate, and medical students have found no differences between men and women in their commitment levels to work and family (Covin & Brush, 1991;Hartung & Rogers, 2000). Spade and Reese (1991) found undergraduate men and women to have equally strong commitments to both work and family life; however, women seemed to place more importance on household roles, and they expected to be employed fewer hours than men did.…”
Section: Gendermentioning
confidence: 93%
“…Research with high school, college, and graduate school students on the relationship between age and year in school and work and family commitment suggests that family commitment may increase with age, whereas both work and family commitment may increase with year in school (Hartung & Rogers, 2000;Kalakoski & Nurmi, 1998;Waterman, 1982;Waterman, Geary, & Waterman, 1974). To focus on those college students for whom work and family commitment are presumably more salient and pressing because of their relatively older age and the imminence of a transition to postcollegiate life, in the present study we limited participation to college juniors and seniors ages 19-23.…”
Section: Age and Year In Schoolmentioning
confidence: 93%
See 1 more Smart Citation
“…Women are increasingly involved in work outside of the home (Marsiglio et al 2000) and young women report placing equal value on their future career roles as do men (Hartung and Rogers 2000;Shu and Marini 1998). Coinciding with this shift in women's work role participation, men are increasingly involved within the family sphere and assuming more responsibility for the direct child-care duties that historically have been the domain of women (Bianchi 2000;Pleck and Masciadrelli 2004;Sandberg and Hofferth 2001).…”
Section: Gender and The Parental Rolementioning
confidence: 94%
“…Malgré cela, Thoits (1992) (Dompierre, 1993;Lyness & Thompson, 1997;Parasuraman, Purohit, Godshalk, & Beutell, 1996). En revanche, même si en apparence les hommes sont plus engagés envers leur travail, lorsque les variables en lien avec la position d'emploi sont contrôlées, les niveaux d'engagement envers le travail s'équivalent chez les deux sexes (Hartung & Rogers, 2000;Marsden, Kalleberg, & Cook, 1993 (Tremblay, 1994). Le travail de « neuf à cinq » ne constitue plus la norme (Johnson et al, 2001) et le travail à temps partiel est la forme d'emploi atypique dont la croissance est la plus rapide actuellement (Bédard & Grignon, 2000;Statistique Canada, 2000).…”
Section: Engagement Dans Les Rôlesunclassified